NEMO–IKKβ Are Essential for IRF3 and NF-κB Activation in the cGAS–STING Pathway - Fang, Run; Wang, Chenguang; Jiang, Qifei; Lv, Mengze; Gao, Pengfei; Yu, Xiaoyu; Mu, Ping; Zhang, Rui; Bi, Sheng; Feng, Ji-Ming; Jiang, Zhengfan (The Journal of immunology (1950), 2017)
Cytosolic dsDNA activates the cyclic GMP-AMP synthase (cGAS)–stimulator of IFN genes (STING) pathway to produce cytokines, including type I IFNs. The roles of many critical proteins, including NEMO, IKKβ, and TBK1, in this pathway are unclear because of the lack of an appropriate system to study. In this article, we report that lower FBS concentrations in culture medium conferred high sensitivities to dsDNA in otherwise unresponsive cells, whereas higher FBS levels abrogated this sensitivity. Based on this finding, we demonstrated genetically that NEMO was critically involved in the cGAS–STING pathway. Cytosolic DNA activated TRIM32 and TRIM56 to synthesize ubiquitin chains that bound NEMO and subsequently activated IKKβ. Activated IKKβ, but not IKKα, was required for TBK1 and NF-κB activation. In contrast, TBK1 was reciprocally required for NF-κB activation, probably by directly phosphorylating IKKβ. Thus, our findings identified a unique innate immune activation cascade in which TBK1–IKKβ formed a positive feedback loop to assure robust cytokine production during cGAS–STING activation.